REHKOPF'S LIST OF WORDS AND PHRASES ILLUSTRATIVE OF PRE-LUKAN SPEECH USAGE - Taylor, Vincent (The journal of theological studies, 1964)
VINCENT TAYLOR; REHKOPF'S LIST OF WORDS AND PHRASES ILLUSTRATIVE OF PRE-LUKAN SPEECH USAGE, The Journal of Theological Studies, Volume XV, Issue 1, 1 April 1964